Debt Management Performance Assessment : Uganda - World Bank (World Bank, Washington, DC, 2020)
A joint World Bank-Macroeconomic and Financial Management Institute of Eastern and Southern Africa (MEFMI)-United Nations Conference for Trade and Development (UNCTAD) mission undertook an assessment of the government’s debt management capacity and institutions in Uganda during March 2018. The objective of the mission was to assess the debt management strengths and areas in need of reform through the application of the debt management performance assessment (DeMPA) methodology. The results of the DeMPA evaluation help the authorities to take stock of the current debt management situation and design medium term priority reforms. This report records the DeMPA in Uganda as of March 2018.